An evaluation of kinesthetic differentiation ability in monofin swimmers - Rejman, M.; Klarowicz, A.; Zaton, K. (Human Movement, 2012)
The aim of this study was to compare the ability of monofin swimmers in reproducing the bending forces that act on a monofin's surface through the specific leg movement present in swimming as well as the forces that the swimmers generated on a kinesthesiometer as part of a dry-land simulation trial. Methods. Six men, members of the National Monofin Swimming Team, took part in the study. The level of the swimmers' kinesthetic response was defined by examining their repeatability in producing the bend forces that act on a monofin's surface as a reaction to water resistance and by investigation on the pressure force generated by a swimmer's lower limbs during dry-land tests on a kinesthesiometer. Results and conclusions. It was established that a high level of kinesthetic response, estimated in the group of monofin swimmers, was the result of an adaptation evoked from the specificity of their sensory stimulus perception, received in the form of feedback from the monofin's large surface area.